Implementation Of Article 86 Of Law Number 13 Of 2003 Concerning Manpower,Occupational Safety And Health Toward Operator Of Gas Station number 21.381.09 At rawa Makmur Of Bengkulu City - Sukma Jumiati; Ganefi Ganefi; Candra Irawan (Universitas Bengkulu, 2022)
Regarding labour protection, therefore the Law Number 13 of 2003 concerning Manpower,Article 86 Paragraph (1) Letter a and Paragraph (2) states that: